Application of the Think Pair Share Learning Model to Improve Learning Achievement of Faith in Qadha' and Qadar Students of Class IX A SMO Negeri 3 Sewon for the 2022/2023 Academic Year - Muhlisin Muhlisin (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
This study aims to determine whether the Think Pair Share (TPS) learning model can improve the learning achievement of PAI Islamic Religious Education on the material Believing in qadho' and qadhar texts of grade IX A SMP Negeri 3 Sewon academic year 2022/2023 This research is a classroom action research consisting of two cycles. Each cycle follows the stages of the Kemmis and Taggart model which includes four components: planning, action, observation, and reflection. The data collected in this study is the result of activities related to the implementation of learning with the Think Pair Share model. Data collection techniques use test and non-test techniques with quantitative and qualitative descriptive approaches. The results showed that the use of the Think Pair Share model in learning activities of Faith in Qadha and Qadhar material can increase student achievement, the percentage of student learning completeness, student learning activities, and teacher activities in the learning process.